The Persian/Arabian Gulf’s sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae) - Moore, Alec B.m.; Compagno, Leonard J.v.; Fergusson, Ian K. (Zootaxa, 2007)
Records of the great white shark Carcharodon carcharias (Linnaeus) (Lamniformes: Lamnidae) in the Persian/Arabian Gulf (hereafter referred to as “The Gulf”) are limited to a single report from Kuwait, in the northwest Gulf, which has subsequently been noted in key references (e.g. Compagno, 2001). Khalaf (1987) recorded C. carcharias based on an observation of a mounted specimen in Kuwait Science and Natural History Museum on a visit there in March 1987. The specimen is reported as being a female C. carcharias of 3m in length, caught off Kuwait’s coast and supplied to the museum on the 14th of April 1984. A black and white photograph of the anterior portion (from just posterior of the pelvic fins) was included in Khalaf’s account (Fig. 1 here), but no measurements or morphological data were presented.